2021
DOI: 10.1038/s41598-021-83927-1
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between cognitive reserve and age moderates effect of lesion load on stroke outcome

Abstract: The concepts of brain reserve and cognitive reserve were recently suggested as valuable predictors of stroke outcome. To test this hypothesis, we used age, years of education and lesion size as clinically feasible coarse proxies of brain reserve, cognitive reserve, and the extent of stroke pathology correspondingly. Linear and logistic regression models were used to predict cognitive outcome (Montreal Cognitive Assessment) and stroke-induced impairment and disability (NIH Stroke Scale; modified Rankin Score) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 47 publications
(25 reference statements)
2
28
0
Order By: Relevance
“…This was particularly important for the language measures since total FHV scores did not correlate with these outcomes (see Table 3 ). While age and education correlated with only some outcome measures, both variables were also included in each of our models based on the assumption that these demographic variables contribute to the variance in confrontational naming ( Neils et al, 1995 , Zec et al, 2007 , Tsang and Lee, 2003 , Henderson et al, 1998 , Welch et al, 1996 ), content production ( Yorkston and Beukelman, 1980 , Cooper, 1990 , Ardila and Rosselli, 1996 , Pistono et al, 2017 , Mackenzie, 2000 ), and stroke severity—in terms of the effect of premorbid neurological function on stroke outcomes ( Umarova et al, 2021 , Umarova et al, 2019 , Habeck et al, 2017 ). The MLRM for NIHSS is reported in Table 4 (Model B), in Table 5 for picture naming, and in Table 6 for content production on Cookie Theft picture description.…”
Section: Resultsmentioning
confidence: 99%
“…This was particularly important for the language measures since total FHV scores did not correlate with these outcomes (see Table 3 ). While age and education correlated with only some outcome measures, both variables were also included in each of our models based on the assumption that these demographic variables contribute to the variance in confrontational naming ( Neils et al, 1995 , Zec et al, 2007 , Tsang and Lee, 2003 , Henderson et al, 1998 , Welch et al, 1996 ), content production ( Yorkston and Beukelman, 1980 , Cooper, 1990 , Ardila and Rosselli, 1996 , Pistono et al, 2017 , Mackenzie, 2000 ), and stroke severity—in terms of the effect of premorbid neurological function on stroke outcomes ( Umarova et al, 2021 , Umarova et al, 2019 , Habeck et al, 2017 ). The MLRM for NIHSS is reported in Table 4 (Model B), in Table 5 for picture naming, and in Table 6 for content production on Cookie Theft picture description.…”
Section: Resultsmentioning
confidence: 99%
“…Elucidating mechanisms of functional improvement from BCI is further complicated by the fact that brain injured patients have widely heterogenous lesions, and lesion size and location do not predict functional outcomes in a straightforward manner (Umarova et al, 2021). Even in patients with similar extents of impairment, lesion location influences performance of BCI decoding of movement intentions (López-Larraz et al, 2017), and the scalp detected signals are qualitatively different when comparing cortical vs subcortical lesions in particular (López-Larraz et al, 2019).…”
Section: Challenges For Elucidating Mechanisms Underlying Bci-induced Functional Improvementsmentioning
confidence: 99%
“…The observed negative effect of age on cognitive stroke recovery has repeatedly been mentioned in the literature. Recently, these effects were also observed for acute stroke patients [45]. A positive impact of education on stroke outcome is known and widely discussed as an indicator of "cognitive reserve" [44], a term comprising acquired mental capacities that have a moderating, protective influence in case of brain damage due to a stroke.…”
Section: Köpssmentioning
confidence: 99%
“…To this end, previous studies intended to identify predictors of stroke outcome. Typical factors related to recovery after stroke are lesion size and location, age, sex, education, and depression [ 3 , 45 ]. Furthermore, the stroke patients’ cognitive status may influence the functional outcome: While some studies found that general cognitive functioning impacted rehabilitation outcomes [ 26 ], others showed that the prevalence and recovery of cognitive deficits after stroke depended on the cognitive domain affected [ 10 ], which include orientation, speech, praxis, attention, visuospatial abilities, processing speed, and executive functions.…”
Section: Introductionmentioning
confidence: 99%